EFFICACY AND TOLERABILITY OF FLUPIRTINE VERSUS TRAMADOL IN THE TREATMENT OF MODERATE CHRONIC LOW BACK PAIN - VINEELA KARTHIK NAGURI; RAVI BABU KOMARAM; TAMILISETTI VIDYA SAGAR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to assess and compare the efficacy and tolerability of flupirtine versus tramadol in patients with chronic moderate low back pain (LBP). Materials and Methods: A prospective study was conducted in the outpatient department of orthopaedics at tertiary care hospital, Rajamahendravarm. After meeting the inclusion criteria, a total of 60 patients were randomly allocated to tablet flupirtine 100 mg in Group A and tablet tramadol 50 mg in Group B. The efficacy of the study drugs was assessed at baseline and the end of treatment by numerical rating scale11, visual analog scale-100 mm, physician’s, and patient’s global assessment. Statistical analysis was done using paired and unpaired t-test and data were presented as mean±standard deviation. Adverse drug reactions were monitored during the treatment. Results: The study results showed that 90% of the patients in Group A and 78% of the patients in Group B had shown a good response to their respective drugs. 30% of flupirtine group patients reported adverse drug reactions which were mild. Conclusion: Both the drugs are effective in the treatment of moderate chronic LBP, but the advantage of flupirtine was, the incidence of adverse drug reactions was less when compared to tramadol group.